Secondary speech therapy prophylaxis aimed at children with low birth weight – a part of research - Gacka, Ewa (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2020)
In the paper, the results of the study of secondary speech therapy prophylaxis aimed at children with low birth weight (preterm babies and babies born at term but with intrauterine growth retardation). The study group consisted of 187 children with a birth weight below 2500 g. Low birth weight is one of the risk factors for various developmental disorders, including disorders of the development of language communication. That is why early identification of the first symptoms of language acquisition (speech development) disorders is so important. The aim of the undertaken research was to analyse the activities in the field of secondary speech therapy prophylaxis, covering this risk group.